(untitled) (Research, Society and Development, 2020)
Understanding education as something dynamic and constantly changing implies the need to consider the historic path that it went through in order to arrive at the current state. Regarding the Chemistry teaching, it is possible to consider that all deployments also involve it, changing the perspectives of the discipline. Thereby, the current outlook of the discipline is the result of previous deployments, also impacting future projections. The research presented here is justified by analyzing the Brazilian educational profile, in order to lead to the understanding of what is currently perceived in the teaching of Chemistry. Therefore, this research aims to briefly analyze the historical path of the Brazilian historical thinking, as well as the contemporary, in order to identify the implications in Chemistry. Initially, we will analyze the historical outlook of the Brazilian education and, later, we will analyze the current teaching and the prospects for the discipline. In order to achieve the proposed objective, the adopted methodology was bibliographic research, by the perception of authors upon books, scientific articles and other published materials that may enrich the study. As a result, the contemporary teaching was perceived as fundamental in the construction of the critic citizen, and Chemistry as an extremely important discipline for the deployment of everyday life, which must be filled with appropriate didactic resources, so that it is increasingly more adequate to the transformations of the society.